X-ray crystal structures, density functional theory and docking on deacetylase enzyme for antiproliferative activity of hispolon derivatives on HCT116 colon cancer. Issue 17 (1st September 2019) - Rossi, Miriam; Caruso, Francesco; Costanzini, Ilaria; Kloer, Carmen; Sulovari, Aron; Monti, Elena; Gariboldi, Marzia; Marras, Emanuela; Balaji, Neduri V.; Ramani, Modukuri V.; Subbaraju, Gottumukkala V.
Graphical abstract: Abstract: The antiproliferative action of hispolon derivatives is stronger than that of related curcumin against several tumor cell lines. Hispolon size, smaller than curcumin, fits better than curcumin into the active site of HDAC6, an enzyme involved in deacetylation of lysine residues. HDACs are considered potential targets for tumor drug discovery and hydroxamates are known inhibitors of HDACs. One of them, SAHA (Vorinostat) is used in clinical studies. Investigations into possible mechanisms for hispolon derivatives active against the HCT116 colon tumor cell line are done after examining the structural results obtained from hispolon X-ray crystal structures as well as performing associated computational docking and Density Functional Theory techniques on HDAC6. These studies show preference for the HDAC6 active site by chelating the Zn center, in contrast with other ineffective hispolon derivatives, that establish only a single bond to the metal center. Structure activity relationships make clear that hydrogenation of the hispolon bridge also leads to single bond (non chelate) hispolon-Zn binding, and consistently nullifies the antiproliferative action against HCT116 tumor.